Pemberdayaan Perempuan dan Pengentasan Kemiskinan Desa Began Lamongan Jawa Timur Melalui Pelatihan Membatik - Sutrisno, Eko; Efendi, Umar; Lailin, Moch. Ichdah Asyarin Hayau; Dewi, Ratnaningrum Zusyana; Ramadhani, Rakhmad Saiful (Yayasan Literasi Sains Indonesia, 2024)
The majority of the people of Began Village make a living as farmers and farmers. Women or wives on average work to take care of the household and, some open businesses buying and selling daily necessities and selling snacks for children. Based on this, the Began Village Government in collaboration with the service team agreed to hold batik training activities for PKK mothers in Began Village. It aims to help improve the economic welfare of the community, diversify income, maintain cultural heritage, and provide opportunities for women's empowerment. The implementation of the service was direct training on how to make batik with 30 participants from the village PKK mothers. The results of the service showed that the knowledge of the villagers in general and the participants of the batik training was quite good. The existence of batik making training made the participants (Ibu PKK) very enthusiastic because they gained new knowledge, such as batik equipment, batik making process and how to care for batik clothes. In addition, participants also gained insight into the types of batik and batik models. Some suggestions and inputs that can be given regarding this service activity are further mentoring on the ability to make batik while motivating the participants in developing their ability to make batik and creating new batik motifs so as to produce distinctive motifs of Began Village.